OUTCOMES OF PNEUMATIC RETINOPEXY PERFORMED BY VITREORETINAL FELLOWS. Issue 1 (January 2019) - Emami-Naeini, Parisa; Vuong, Vivian S.; Tran, Steven; Morse, Lawrence S.; Moshiri, Ala; Park, Susanna S.; Yiu, Glenn
Abstract : Purpose: To evaluate the anatomical and visual outcomes of patients who underwent pneumatic retinopexy by vitreoretinal fellows. Methods: We included 198 eyes (198 patients) that underwent pneumatic retinopexy by vitreoretinal fellows at a single academic institution between November 2002 and June 2016. Main outcomes were single-operation success and final anatomical success in retinal reattachment, as well as visual acuity at 3 months and 6 months after treatment. Results: Single-operation success rate was 63.6% at 3 months and 59.5% at 6 months. Final anatomical reattachment was achieved in 92.9% (n = 184) and 96.6% (n = 143) at 3 months and 6 months, respectively. Logarithm of the minimum angle of resolution visual acuity improved from 0.72 ± 0.1 (∼20/100 Snellen) at baseline to 0.36 ± 0.06 (∼20/40 Snellen) at 6 months ( P < 0.001). There was no statistical difference in anatomical success rates or visual outcomes between cases performed by first- or second-year fellows ( P > 0.50). Single-operation success was associated only with size of detachment ( P = 0.01). Visual outcome was associated with macula status at baseline ( P = 0.032) and number of reoperations ( P < 0.001). Conclusion: Anatomical and visual outcomes of fellow-performed pneumatic retinopexy are comparable with those reported in the previous literature. Abstract : This retrospective study was conducted to evaluate outcomes of pneumatic retinopexy performed by vitreoretinal fellows in training. The authors showed that visual and anatomical outcomes of fellow-performed pneumatic retinopexy are comparable with those previously reported in the literature.